In vitro tolerance of rice pathogen Rhizoctonia solani by orchid mycorrhizal fungi isolated from orchids in BRIS, Setiu Wetlands - Nurul Aliaa,; Siti Noradila A.G.,; Zaiti M.Z.,; Fatin Syakirah S., (Penerbit Universiti Kebangsaan Malaysia, 2019)
Rice (Oryza sativa) is a major staple food that feeds more than half of the human population in the world. However, rice production faces major loss in yield due to rice diseases including Rice Sheath Blight (RSB), which is caused by a soil-borne fungal pathogen, Rhizoctonia solani. Interestingly, the same pathogenic R. solani in rice has also been isolated from orchids and is known to form a vital symbiotic relationship, called orchid mycorrhiza. Thus, this study aims at isolating and identifying the orchid mycorrhizal fungi (OMF) present in roots of orchids at beach ridges interspersed with swales (BRIS), Setiu Wetlands and to determine their antagonistic activity towards pathogenic R. solani through dual culture bioassay. Mycorrhizal fungi were isolated from the roots of Phalaenopsis pulcherrima, Bromheadia finlaysoniana and Dendrobium crumenatum. Three isolates were identified through morphological identification to be Rhizoctonia species namely A, B and C along with one fungal isolate as Daldinia species. In vitro antagonistic test against pathogenic R. solani showed Rhizoctonia species (B) displayed the strongest anti-fungal activity with 60.46% of Percentage Inhibition of Radial Growth (PIRG) value followed by Rhizoctonia species (C) with 59.9%, Rhizoctonia species (A) with 51.02% and Daldinia species with 39.80%. This preliminary investigation shows the potential of orchid mycorrhizal fungi to be developed as a biocontrol agent.